Tourism and Islamic hospitality: measuring halal attributes, satisfaction and expectations of Muslim tourists - Anas Pattaray; Herman Herman (Jurnal Pariwisata Pesona, 2024)
This study aims to determine the relationship of halal attributes to the satisfaction and expectations of tourists visiting Lombok. This research was conducted to illustrate that halal attributes can be used as a reference for developing facilities and services that suit the needs of Muslim tourists. This research uses a qualitative approach by conducting in-depth interviews to determine attributes that are in accordance with the characteristics of the island of Lombok and using a quantitative approach by distributing questionnaires to tourists. The results showed that there is a positive relationship between halal attributes and tourists' satisfaction and expectations as well as their relationship with friendship. Suggestions that can be given based on the results of this study are the need to improve the quality of halal attributes by paying attention to the motivation of tourists visiting Lombok Island.